COVID-19 and Substance Use: A Scientometric Assessment of Global Publications During 2020 and 2021. Issue 1 (March 2022) - Grover, Sandeep; Gupta, B.M.; Ahmed, K.K. Mueen
Aim: This study aimed to assess the characteristics and trends of research on substance use and COVID-19. Methods: Keywords related to "Covid-19" and "Substance Use" were used in a search query formulated for the Scopus search engine. The articles published during the years 2020 and 2021, through early November 2021, were considered. Results: A total of 2184 publications were published on this topic, averaging 9.69 citations per paper. About one-seventh (13.96%) share of global publications was supported by extramural funding support. The maximum number of publications emerged from the United States of America (USA) ( n = 831; 38.05%), followed by the United Kingdom (UK) ( n = 212; 9.71%), India ( n = 165; 7.55%), and Canada (155 papers; 7.10%). In terms of citation impact, publications emerging from China (24.42 and 2.52) had the highest citation impact, followed by publications emerging from Australia (18.83 and 1.94), France (16.48 and 1.70), the UK (15.44 and 1.59), Italy (13.36 and 1.38), and Canada (12.73 and 1.31). When the data in terms of specific institutes were evaluated, Harvard Medical School, USA ( n = 52), was ranked first in productivity, followed by the University of Toronto, Canada ( n = 47); the Yale School of Medicine, USA ( n = 35); INSERM, France ( n = −29); and the University of British Columbia, Canada ( n = 2s). The University College London, UK (30.24 and 3.12), ranked first in citation impact, followed by INSERM, France (22.0 and 2.27); the Sapienza University of Rome, Italy (17.4 and 1.8); and the University of Toronto, Canada (13.68 and 1.41). When the journals were evaluated, the International Journal of Environmental Research and Public Health ( n = 83) ranked first in publication productivity, followed by the Journal of Substance Abuse Treatment ( n = 73), Frontiers in Psychology ( n = 39), Drug and Alcohol Dependence ( n = 28), and International Journal of Drug Policy ( n = 26). Conclusion: This bibliometric study suggests that a large amount of literature has accumulated during the COVID-19 pandemic on substance use disorders, both from developed and developing countries.